The Relationship between Phylogenic Typing and Antimicrobial Susceptibility Patterns for Escherichia coli Isolated from UTIs in Many Hospitals at Baghdad City - Eptisam Younam Pirko (Journal of Global Pharma Technology, 2018)
Escherichia coli are one of the most important pathogens, associated with urinary tract infections. Four phylogenetic groups were identified with locally isolates divided as follows: the phylogroups B2 43%, phylogroups D 28.25%, phylogroups A 24% and B1 3.5%, so phylogenic group B1 was prevalent among male patients of AL-Yarmouk hospital 14%, followed AL-Iskan 3.75 % as well, isolation rate of E.coli were higher among age 11-20 years 31.75 %, of which 11% were sensitivity to antibiotics, while 75.25% were classified as extensive drug resistance pathogens, but 13.75% were multidrug resistance and in Karkh areas, the frequency of phylogenetic B2 was 59.88%, followed phylogenetic A and D were 68.75 and 48.78% respectively as compared to Rusafa areas were prevalence phylogenetic B2 40.12% , followed phylogenetic D and A were 51.22 and 31.25 %, as well as most of these phylogenetic groups occurred more frequently in both groups B2 or D 43, 28.25% respectively, also 2.75, 2.5% of phylogenic A were antibiotics sensitivity in both AL-Iskan hospital and Ghazi AL-Hariri hospital respectively whilst these phylogenic was multidrug resistance as percentage 9, 3.75 % Alternately in both AL-Yarmouk hospital and AL-Iskan hospital, Whilst in these hospital this phylogenic A was founded with extensive drug resistance 1, 0.75% respectively, also most of phylogenetic group B2 occurred more frequently in AL-Yarmouk hospital, so the sensitivity; multidrug resistance and extensive drug resistance as 2.25, 15 and 3.5% respectively, also all phylogenetic groups E. coli isolates from UTI patients of five hospital were grouped in two or three major group as A, B group contain major sub groups. The aim of this study is to explore the prevalence of in Escherichia coli from urinary tract infections in many Baghdad hospitals, investigate their phylogenic groups and evaluate the relationship of phylogenic groups of E. coli isolates with the antibiotic resistant patterns.